LITERASI KEUANGAN DAN PERILAKU KEUANGAN YANG MEMPENGARUHI KEPUTUSAN INVESTASI MELALUI PENGELOLAAN KEUANGAN SEBAGAI VARIABEL INTERVENING PADA MAHASISWA PENERIMA KIP DI UNIVERSITAS ABDURACHMAN SALEH SITUBONDO ANGKATAN TAHUN 2020 - Azzuhro, Elok Ferina Yuan; Wiryaningtyas, Dwi Perwitasari; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2023)
Investment decisions among students are the most important element to avoid consumptive behavior from the funds obtained. The purpose of this study is to analyze and test financial literacy and financial behavior that influence investment decisions through financial management as an intervening variable in students receiving KIP at Abdurachman Saleh Situbondo University. The sample used was 72 KIP recipient students at Abdurachman Saleh Situbondo University class of 2020. The sampling technique was determined by Purposive Sampling . Data analysis and hypothesis testing in this study used the Structural Wquation Model – Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that Financial literacy has a significant positive effect on Financial management, Financial behavior has a significant positive effect on Financial management, Financial literacy has a positive but not significant effect on Investment decisions, Financial behavior has a significant positive effect on Investment decisions, Financial management has a significant positif effect on Investmen decisions. The result of the indirect hypothesis test show that Financial literacy has a significant positive effect on investment decisions through Financial management, Financial behavior has a positive but not significant effect on Investmen decision through Financial management.